2012
DOI: 10.1002/dneu.22064
|View full text |Cite
|
Sign up to set email alerts
|

Fetuin‐A in the developing brain

Abstract: The serum protein fetuin-A is essential for mineral homeostasis and shows immunomodulatory functions, for example by binding to TGF superfamily proteins. It proved neuroprotective in a rat stroke model and reduced lethality after systemic lipopolysaccharide challenge in mice. Serum fetuin-A concentrations are highest during intrauterine life. Different species show intrauterine cerebral fetuin-A immunoreactivity, suggesting a contribution to brain development. We therefore aimed at specifying fetuin-A immunore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 44 publications
3
17
0
Order By: Relevance
“…When up-regulated, the enzyme has been shown to increase the glycolytic pathway and decrease the pentose phosphate pathway, increasing oxidative stress, and apoptotic neuronal death [ 88 , 89 ]. Alpha-2-HS-glycoprotein, also known as fetuin-A (down-regulated; p < 0.0005), is a neuroprotective protein the function of which has been demonstrated in a rat stroke model [ 90 ] and in early brain ischemic injury, whereby it attenuates the brain inflammatory response [ 91 ]. It has also been shown to play a part in brain development [ 90 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When up-regulated, the enzyme has been shown to increase the glycolytic pathway and decrease the pentose phosphate pathway, increasing oxidative stress, and apoptotic neuronal death [ 88 , 89 ]. Alpha-2-HS-glycoprotein, also known as fetuin-A (down-regulated; p < 0.0005), is a neuroprotective protein the function of which has been demonstrated in a rat stroke model [ 90 ] and in early brain ischemic injury, whereby it attenuates the brain inflammatory response [ 91 ]. It has also been shown to play a part in brain development [ 90 ].…”
Section: Discussionmentioning
confidence: 99%
“…Alpha-2-HS-glycoprotein, also known as fetuin-A (down-regulated; p < 0.0005), is a neuroprotective protein the function of which has been demonstrated in a rat stroke model [ 90 ] and in early brain ischemic injury, whereby it attenuates the brain inflammatory response [ 91 ]. It has also been shown to play a part in brain development [ 90 ]. Hence, the up-regulation of 6-phosphofructokinase type C and down-regulation of fetuin-A suggest an increased oxidative stress in the olfactory bulb, which may explain the increased neuronal cell death, as previously demonstrated by Deng et al [ 85 ].…”
Section: Discussionmentioning
confidence: 99%
“…After affinity purification of serum using the ASD1 peptoid, and observation of this analyte by Coomassie Blue staining after gel electrophoresis, we found a single band whose mass does not correspond with an antibody fragment. After sequencing this band, we identified two nonantibody proteins that were pulled down by the ASD1 peptoid: (1) Fetuin-A, a glycoprotein primarily involved in mineral homeostasis, has been suggested to play a neuroprotective role in the developing brain (Elsas et al, 2013). In addition, mutations in Fetuin-A's corresponding gene have recently been linked to a developmental disorder (3q27.3) exhibiting some autistic features (Thevenon et al, 2014).…”
Section: Peptoid-antibody Identificationmentioning
confidence: 99%
“…The distribution of fetuin-A in the developing brain was examined in various species. In the developing neocortex fetuin-A co-localized with a population of cells that migrated from the ventricular zone to form the primordial plexiform layer and the early cortical plate [ 17 , 20 23 ]. Dziegielewska and colleagues [ 22 ] observed that the distribution of fetuin-A in the early cortical plate of human embryos of 7 weeks and sheep embryos of 35–36 days was very similar.…”
Section: Introductionmentioning
confidence: 99%
“…In human fetuses of 33 weeks of gestational age, fetuin-A staining was negative. Previously, we examined the distribution of fetuin-A in the brain of human and rat fetuses and in newborns [ 23 ]. In human tissue, fetuin-A staining decreased with age, but still was found in the cortex of term born neonates.…”
Section: Introductionmentioning
confidence: 99%